EFFECTS OF LAND-BASED STRATEGIES FOR CLIMATE CHANGE MITIGATION, ADAPTATION ON MAIZE FARMER’S PRODUCTION: A STUDY OF WORLD BANK INTERVENTION IN NORTHWEST, NIGERIA - Atama, Alexander Abine; OTARU, Abdulkabir Onoruoyiza; Amanabo, Sarah Ojoma; Akuh, Omojo Isabella; AFOLABI, Ekundayo (FUDMA Journal of Sciences, 2026)
Farmers’ land-based decisions relating to climate change mitigation and adaptation depend on the major production motive: land conservation or revenue maximization. This study evaluates the effectiveness of World Bank-led land management strategies in mitigating climate change effects and enhancing adaptation among maize farmers in Northwest Nigeria. Multi-stage and purposive sampling techniques were employed; 540 maize farmers were randomly selected. The specific objectives; describe the sociocultural, determine the effects on maize farmer’s production output. Results showed that the decision option of 61% of the farmers with a mean farm size of 2.54 hectares and maize value of N3,071,185.70k were classified unsustainable, while the decision option of the remaining 39.44% were classified sustainable, with a mean farm size of 1.57 hectares and maize value of N1,209,461.95k. The percentage outputs as normalized by 1.56 hectares were 0% for sustainable land-based option and 56.95% for unsustainable land-based option. The coefficients of labour (-1.147) and amount spent on manual weeding (-3.926) of the estimated SUR equations for sustainable land-based decision option were negative and statistically significant at 1% level. Thus, stakeholders in sustainable land management in collaboration with World Bank should develop simple labour-saving, sustainable motorized weeding tools to encourage sustainable land-based practices in maize farming. Considering the high value of maize generated under unsustainable land-based decision option due to inorganic fertilizer use and the need to reduce greenhouse gas emission, extension workers and stakeholders in agronomy and soil management should educate farmers on yield enhancement through appropriate and efficient use of organic manure.